Constraints and Prospects of Small Scale Industries in Punjab: An Analytical Study - BEDI, Dr. UBIQUE; SINGH, Dr. INDERPAL; SAMPLA, Dr. RUPINDER; SINGH, Dr TARUNJIT (The journal of contemporary issues in business and government, 2021)
Small scale industries are well recognised for its contribution to innovation, employment and economic dynamism. Small firms have been the chief source of creating new jobs in almost all the developed countries. It has been seen that number of existing industries in Punjab has been dominated by small scale firms. Despite the recognition of significant role played by small scale industries in economy, some critical barriers prevent them from developing and contributing sufficiently. The present paper attempts to find out the major constraints faced by small scale industries selected from five sub sectors i.e. Machinery Parts, Hand tool, Spare Parts, Auto Parts and Pipe fitting industries in Jalandhar district. Data was collected through primary sources by framing a well structured questionnaire. Factor Analysis was applied on data to get the authentic results. The results revealed that the five major factors that affect the growth and development of small scale firms are Power Constraints, Approach up to Local Market, Absence of Effective Administrative Support, Lack of Basic Facilities and Financial Constraints.